Modern Chinese Vocabulary – Morpheme and Word - Haryanti, Sri (Humaniora, 2014)
Vocabulary is a foundation of a language. Like a building that cannot stand without having a foundation, neither can a sentence be formed without vocabulary. In learning a language, the more students are able to expand their vocabulary knowledge, the better they will gain proficiency in using the language. Specifically, when learning Mandarin, students must understand clearly what morpheme and word and the difference between morpheme and words as well as their relevant application. Consequently, as students improve their vocabulary knowledge and its application, they will be able to express better language proficiency. This paper used literature and observational study.